Asymmetry and rehabilitation of the subjective visual vertical in unilateral vestibular hypofunction patients - Haijoub, Souad; Hautefort, Charlotte; Toupet, Michel; Lacour, Michel (Frontiers in Systems Neuroscience, 2024)
Aims : Patients with acute unilateral peripheral vestibular hypofunction (AUVP) show postural, ocular motor, and perceptive signs on the diseased side. The subjective visual vertical (SVV) test measures the perceived bias in earth-vertical orientation with a laser line in darkness.This study was aimed at 1) examining whether SVV bias could depend on preset line orientation and angles, and 2) investigating whether vestibular rehabilitation (VR) can improve SVV normalization. SVV symmetry/asymmetry and impact of VR on SVV normalization have never been documented in the literature.We investigated the SVV bias in a retrospective study (Study 1 ) comparing the data recorded for line orientation to the ipsilateral and contralateral sides at preset angles of 15° and 30°. We investigated the effects of VR on SVV normalization in a prospective study (Study 2 ) in which patients were tilted in the roll plane using a support tilted to the hypofunction side with the same amplitude as the SVV bias. This VR protocol was performed twice a week for four weeks. Supplementary data on body weight distribution and medio-lateral position of the center of foot pressure (CoP) were obtained using posturography recordings.Results : Study 1 showed asymmetrical values of the SVV bias. On average, the SVV errors were significantly higher for ipsilateral compared to contralateral line orientation , and for 30° compared to 15° preset angle. Study 2 showed a fast SVV normalization with VR. Non-pathological SVV bias was found after only 3 to 5 VR sessions while pathological SVV values were still observed at the same time in patients without VR . A close temporal correlation was observed in the time course of body weight distribution, mediolateral CoP position, and SVV bias over time, suggesting beneficial effects of the VR protocol at both the perceptive and postural levels. We recommend routine assessment of the ipsilateral and contralateral SVV bias separately for a better evaluation of otolith organs imbalance. The SVV bias and the postural impairment can be rapidly normalized with the tilted protocol. The protocol likely reweights the visual and somatosensory cues involved in the perception of verticality.